Self-perception of patients with fibromyalgia on the physiotherapy treatment - Fernanda Gadelha Severino; Rodrigo Aguiar Simões; Glauter José Silveira Araújo; Maria Albertina Rocha Diógenes (Universidade de Fortaleza, 2014)
Objective: To understand the self-perception of the patient with fibromyalgia regarding the pathology and physiotherapy and show it as an instrument for improving the practice of health professionals. Methods: A qualitative, exploratory and descriptive research conducted at a physiotherapy center in the municipality of Fortaleza, Ceará, in 2013. The study comprised 10 people with a clinical diagnosis of fibromyalgia undergoing physiotherapy treatment. Data were collected through semi-structured interview and underwent content analysis. The text could be grouped into the following themes: Relationship between pain and fatigue; Fibromyalgia defined as a personal, physical and mental pain; Physiotherapy, the functional workshop of the body; The idea of being healthy and uncertainty; and the humanized physiotherapist. Results: Pain was reported as the most disabling factor and, because of that, they feel tired and stressed. They understand the importance of physiotherapy in the process of adaptation to physical limits and coping with pain, and recognize the physiotherapist as a humanized professional. Conclusion: The reports show that patients undergoing physiotherapy recognize they are sick and know the importance of physiotherapy for their functional condition. The speeches give a feedback to the professional who identifies the objectives and factors that interfere with treatment, and may also suggest the need for interventions by other professionals. doi:0.5020/18061230.2014.p183